Ependymal Cilia: Physiology and Role in Hydrocephalus - Ji, Weiye; Tang, Zhi; Chen, Yibing; Wang, Chuansen; Tan, Changwu; Liao, Junbo; Tong, Lei; Xiao, Gelei (Frontiers in Molecular Neuroscience, 2022)
Cerebrospinal fluid (CSF), a colorless liquid that generally circulates from the lateral ventricles to the third and fourth ventricles, provides essential nutrients for brain homeostasis and growth factors during development. As evidenced by an increasing corpus of research, CSF serves a range of important functions. While it is considered that decreased CSF flow is associated to the development of hydrocephalus, it has recently been postulated that motile cilia, which line the apical surfaces of ependymal cells (ECs), play a role in stimulating CSF circulation by cilia beating. Ependymal cilia protrude from ECs, and their synchronous pulsing transports CSF from the lateral ventricle to the third and fourth ventricles, and then to the subarachnoid cavity for absorption. As a result, we postulated that malfunctioning ependymal cilia could disrupt normal CSF flow, raising the risk of hydrocephalus. This review aims to demonstrate the physiological functions of ependymal cilia, as well as how cilia immobility or disorientation causes problems. We also conclude conceivable ways of treatment of hydrocephalus currently for clinical application and provide theoretical support for regimen improvements by investigating the relationship between ependymal cilia and hydrocephalus development.